An update on the validation of whole slide imaging systems following FDA approval of a system for a routine pathology diagnostic service in the United States. (18th August 2017) - Boyce, BF
Abstract: Pathologists have used light microscopes and glass slides to interpret the histologic appearance of normal and diseased tissues for more than 150 years. The quality of both microtomes used to cut tissue sections and microscopes has improved significantly during the past few decades, but the process of rendering diagnoses has changed little. By contrast, major advances in digital technology have occurred since the introduction of hand held electronic devices, including the development of whole slide imaging (WSI) systems with software packages that can convert microscope images into virtual (digital) slides that can be viewed on computer monitors and via the internet. To date, however, these technological developments have had minimal impact on the way pathologists perform their daily work, with the exception of using computers to access electronic medical records and scholarly web sites for pertinent information to assist interpretation of cases. Traditional practice is likely to change significantly during the next decade, especially since the Federal Drug Administration in the USA has approved the first WSI system for routine diagnostic practice. I review here the development and slow acceptance of WSI by pathology departments. I focus on recent advances in validation of WSI systems that is required for routine diagnostic reporting of pathology cases using this technology.